Current collector, preparation method thereof and lithium battery
By using a composite of high specific heat capacitance material and high compaction material as the current collector in lithium-ion batteries, the problem of insufficient thermal management capabilities of the current collector is solved, and higher thermal management and safety performance in high energy density applications are achieved.
Patent Information
- Application Number
- CN202411339659.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
AI Technical Summary
Existing lithium-ion battery current collectors lack thermal management capabilities in high energy density applications, resulting in safety problems, especially in high-temperature external short circuits or thermal abuse, which may lead to thermal runaway and fire.
Use high specific heat capacity materials such as potassium nitrate, high melting point paraffin and composites of carbon nanotubes and high compaction materials such as alumina and magnesium oxide as current collectors, and improve thermal management capabilities by absorbing reaction heat inside the battery cell to delay temperature rise. and safety performance.
Effectively absorb and slowly release the internal heat of the battery, reduce the risk of thermal runaway, and improve the safety performance and thermal stability of the battery under high temperature and high temperature external short circuit conditions.
Smart Images

Figure CN119297288A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a current collector and a preparation method thereof, and a lithium battery. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles and energy storage systems due to their high energy density, long cycle life and low self-discharge rate. However, as energy density continues to increase, battery safety issues are becoming more prominent. High energy density means that more energy is stored per unit volume or mass, which may cause a large amount of heat to be generated inside the battery when the battery is overcharged, short-circuited, thermally abused or other abnormal conditions occur. If this heat cannot be effectively dissipated, the battery temperature will rise sharply, causing thermal runaway, and even fire or explosion.
[0003] In order to address the issue of battery safety, researchers have proposed a variety of improvement plans, one of which is to use a current collector containing a flame retardant. Current research has found that a single flame retardant has limitations in improving the flame retardant properties and overall effects of the battery. For example, when the battery undergoes high-temperature external short circuit, thermal abuse and other tests, a single flame retardant solution often cannot effectively dissipate the generated heat quickly. This is because the effect of the flame retardant is mainly focused on delaying the spread of the flame, but there are still deficiencies in how to quickly and effectively reduce the overall temperature of the battery and effectively dissipate the heat. In addition, the introduction of flame retardants may affect the electrical conductivity and thermal conductivity of the current collector, thereby restricting its effectiveness in practical applications.
[0004] Therefore, although the current collectors have made some progress in improving battery energy density and safety, the current collectors still have obvious deficiencies in specific heat capacity. This problem limits their effectiveness in high energy density battery applications. In order to ensure the safety of batteries in high energy density applications, it is urgent to develop current collector materials with higher specific heat capacity while maintaining good electrical and thermal conductivity. Summary of the invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a current collector, which realizes the use of a current collector with a high specific heat capacity, and absorbs part of the reaction heat when the reaction heat is generated inside the battery cell, delays the temperature rise inside the battery cell, and slowly accumulates the heat, thereby improving the thermal shock passing temperature and high temperature short performance of the lithium-ion battery, and ultimately improving the safety performance of the battery cell.
[0006] The invention also provides a method for preparing a current collector.
[0007] The invention also provides a battery pole piece.
[0008] The invention also provides a lithium ion battery.
[0009] The first aspect of the present invention provides a current collector, comprising a substrate and a metal layer arranged on the surface of the substrate, wherein the components of the substrate include a high specific heat capacity material A and a high-density material B, wherein the high specific heat capacity material A includes at least one of potassium nitrate, high melting point paraffin and carbon nanotubes, and the high-density material B includes at least one of aluminum oxide and magnesium oxide.
[0010] One of the technical solutions of the present invention regarding the current collector has at least the following beneficial effects:
[0011] When lithium batteries are undergoing safety tests, such as thermal abuse / high temperature external short circuit, the temperature rise of external temperature or short circuit will cause chemical reactions inside the battery cell, thereby generating reaction heat. The accumulation of reaction heat that cannot be released will cause the temperature inside the battery cell to rise sharply until the lithium cobalt oxide decomposes, the battery cell catches fire, and the test fails. According to the simplified model of heat generation and heat dissipation balance during battery operation, Q-δ=mCp.m(dT / dt), Q represents the battery heat generation rate; δ represents the heat dissipation rate; m represents the mass; Cp.m(dT / dt) represents the rate of change of battery temperature over time. The larger the specific heat capacity, the less likely it is to fail due to heat. The present invention utilizes potassium nitrate with large specific heat capacity, high melting point paraffin, carbon nanotubes and aluminum oxide and magnesium oxide with good pressure resistance to provide a lithium ion battery current collector solution with high specific heat capacity. The current collector containing high specific heat capacity can absorb part of the reaction heat when the reaction heat is generated inside the battery cell, delay the temperature rise inside the battery cell, and slowly accumulate the heat, thereby improving the thermal shock pass temperature and high temperature short circuit performance of the lithium ion battery, and ultimately improving the safety performance of the battery cell.
[0012] According to some embodiments of the present invention, the mass ratio of the high specific heat capacity material A to the high compaction material B is 1:0.5-1.5.
[0013] According to some embodiments of the present invention, the mass ratio of the high specific heat capacity material A and the high compaction material B is any value of 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or a range formed by any two of them, such as 1:0.5 to 1.0.
[0014] According to some embodiments of the present invention, when the current collector is a positive electrode current collector, the metal layer is an aluminum layer.
[0015] According to some embodiments of the present invention, when the current collector is a negative electrode current collector, the metal layer is a copper layer.
[0016] According to some embodiments of the present invention, the thickness of the substrate is 1.5 μm to 2.5 μm.
[0017] According to some embodiments of the present invention, the thickness of the substrate is any one of 1.5 μm, 2.0 μm, and 2.5 μm, or a range formed by any two of the values.
[0018] According to some embodiments of the present invention, the thickness of the metal layer is 4 μm to 6 μm.
[0019] According to some embodiments of the present invention, the thickness of the metal layer is any one of 4 μm, 5 μm, and 6 μm, or a range formed by any two of them.
[0020] According to some embodiments of the present invention, the high specific heat capacity material A has a specific heat capacity of 1 J / g·K to 2.4 J / g·K.
[0021] According to some embodiments of the present invention, the specific heat capacity of the high-density material B is between 0.75 J / g·K and 0.90 J / g·K.
[0022] According to some embodiments of the present invention, the compacted density of the high specific heat capacity material A is 1.3 g / cm 3 ~1.8g / cm 3 .
[0023] According to some embodiments of the present invention, the compaction density of the high compaction material B is 4 g / cm 3 ~6.0g / cm 3 .
[0024] The second aspect of the present invention provides a method for preparing the current collector of the first aspect of the present invention, comprising the following steps:
[0025] S1: mixing the powders of the high specific heat capacity material A and the high compaction material B in proportion, adding epoxy resin and curing agent, stirring, and curing and molding in a mold to obtain the matrix;
[0026] S2: Arranging the metal layer on the surface of the substrate to obtain the current collector.
[0027] A technical solution in the preparation method of the current collector of the present invention has at least the following beneficial effects:
[0028] The preparation method of the present invention does not require expensive equipment and complicated process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, and is easy to industrialize.
[0029] According to some embodiments of the present invention, the curing agent comprises a polythiol-modified amine.
[0030] Polythiol modified amine is a highly flexible curing agent that can keep the substrate flexible and facilitate production and processing.
[0031] A third aspect of the present invention provides a lithium-ion battery pole piece, comprising the current collector of the second aspect of the present invention and an active material layer disposed on the surface of the current collector.
[0032] The lithium-ion battery pole piece of the present invention, because the current collector of the present invention is used, has at least the following beneficial effects:
[0033] Improved thermal management capabilities of the battery. Since the current collector uses a high specific heat capacity material, it can effectively absorb and slowly release the heat generated inside the battery, thereby slowing down the temperature rise of the battery and improving the thermal stability and safety of the battery. By improving the thermal management of the battery, the risk of thermal runaway is reduced and the safety performance of the battery under high temperature or thermal abuse conditions is enhanced.
[0034] According to some embodiments of the present invention, when the lithium-ion battery pole piece is a positive pole piece, components of the active material layer include a positive electrode material, a positive electrode conductor and a positive electrode binder.
[0035] According to some embodiments of the present invention, the positive electrode material includes lithium cobalt oxide.
[0036] According to some embodiments of the present invention, the positive electrode conductive agent includes acetylene black.
[0037] According to some embodiments of the present invention, the positive electrode binder includes polyvinylidene fluoride.
[0038] According to some embodiments of the present invention, the mass ratio of the positive electrode material, the positive electrode conductor and the positive electrode binder may be 98:1.2:0.8.
[0039] According to some embodiments of the present invention, a method for preparing a positive electrode sheet includes:
[0040] The positive electrode material, positive electrode conductive agent and positive electrode binder are fully stirred and mixed in an N-methylpyrrolidone solvent system, and then coated on an aluminum foil, and then dried, rolled and slit to obtain a positive electrode sheet.
[0041] According to some embodiments of the present invention, when the lithium-ion battery pole sheet is a negative electrode pole sheet, the components of the active material layer include a negative electrode material, a negative electrode conductor, a negative electrode binder and a thickener.
[0042] According to some embodiments of the present invention, the negative electrode material comprises graphite.
[0043] According to some embodiments of the present invention, the negative electrode conductive agent includes acetylene black.
[0044] According to some embodiments of the present invention, the negative electrode binder includes styrene-butadiene rubber.
[0045] According to some embodiments of the invention, the thickener comprises sodium carboxymethyl cellulose.
[0046] According to some embodiments of the present invention, the mass ratio of the negative electrode material, the negative electrode conductor, the negative electrode binder and the thickener may be 98.1:0.5:0.7:0.7.
[0047] According to some embodiments of the present invention, a method for preparing a negative electrode sheet includes:
[0048] The negative electrode material, negative electrode conductive agent, negative electrode binder and thickener are fully stirred and mixed in a deionized water solvent system, and then coated on a copper foil, and then dried, rolled and slit to obtain a negative electrode sheet.
[0049] A fourth aspect of the present invention provides a lithium-ion battery, comprising a separator, an electrolyte, and the lithium-ion battery pole pieces of the third aspect of the present invention, wherein the lithium-ion battery pole pieces comprise a positive pole piece and a negative pole piece.
[0050] The lithium-ion battery of the present invention, because it uses the battery pole piece of the present invention, has at least all the beneficial effects of the battery pole piece.
[0051] According to some embodiments of the present invention, the separator comprises a polyethylene (PE) porous polymer film. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a schematic diagram of the cross-sectional structure of the current collector in Example 1. DETAILED DESCRIPTION
[0053] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0054] In the first aspect, in some embodiments of the present invention, a current collector is provided, comprising a substrate and a metal layer arranged on the surface of the substrate, wherein the components of the substrate include a high specific heat capacity material A and a high-density material B, wherein the high specific heat capacity material A includes at least one of potassium nitrate, high melting point paraffin and carbon nanotubes, and the high-density material B includes at least one of aluminum oxide and magnesium oxide.
[0055] It is understandable that when lithium batteries are undergoing safety tests, such as thermal abuse / high temperature external short circuit, the temperature rise of external heating or short circuit will cause chemical reactions inside the battery cell, thereby generating reaction heat. The accumulation of reaction heat that cannot be released will cause the temperature inside the battery cell to rise sharply until the lithium cobalt oxide decomposes, the battery cell catches fire, and the test fails. According to the simplified model of heat generation and heat dissipation balance during battery operation, Q-δ=mCp.m(dT / dt), Q represents the battery heat generation rate; δ represents the heat dissipation rate; m represents the mass; Cp.m(dT / dt) represents the rate of change of battery temperature over time. The larger the specific heat capacity, the less likely it is to fail due to heat. The present invention utilizes potassium nitrate with large specific heat capacity, high melting point paraffin, carbon nanotubes and aluminum oxide and magnesium oxide with good pressure resistance to provide a lithium ion battery current collector solution with high specific heat capacity. The current collector containing high specific heat capacity can absorb part of the reaction heat when the reaction heat is generated inside the battery cell, delay the temperature rise inside the battery cell, and slowly accumulate the heat, thereby improving the thermal shock pass temperature and high temperature short circuit performance of the lithium ion battery, and ultimately improving the safety performance of the battery cell.
[0056] In combination with the first aspect, in some embodiments of the present invention, the mass ratio of the high specific heat capacity material A to the high compaction material B is 1:0.5-1.5.
[0057] In combination with the first aspect, in some embodiments of the present invention, the mass ratio of high specific heat capacity material A and high compaction material B is any value of 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or a range value formed by any two of them, such as 1:0.5 to 1.0.
[0058] It should be noted that when designing lithium-ion battery current collectors, the mass ratio of high specific heat capacity material A (such as potassium nitrate, high melting point paraffin, carbon nanotubes) and high compaction material B (such as aluminum oxide, magnesium oxide) is crucial to the thermal performance of the material and the overall battery safety. Specifically:
[0059] If the mass ratio is less than 1:0.5, it may lead to insufficient heat dissipation performance, material cost and stability problems. If the proportion of high specific heat capacity material A is high (such as potassium nitrate, high melting point paraffin or carbon nanotubes), although these materials have high specific heat capacity, their heat dissipation performance and high temperature resistance may be insufficient. The high specific heat capacity of material A may not be able to effectively convert and dissipate heat, resulting in insufficient heat dissipation capacity. When a chemical reaction occurs inside the battery and heat is generated, the current collector may not be able to effectively absorb and dissipate the reaction heat, causing the internal temperature of the battery to rise rapidly, thereby increasing the risk of thermal failure. The cost of high specific heat capacity material A (such as high melting point paraffin, carbon nanotubes) is generally high, and their pressure resistance and chemical stability may also be low. Excessive proportion of material A may lead to a significant increase in the cost of the overall material, and may affect the stability and structural integrity of the current collector. High costs will increase the overall production cost of the battery, and stability issues may affect the long-term reliability and safety of the battery.
[0060] If the mass ratio is greater than 1:1.5, the specific heat capacity benefit may decrease and the mechanical and processing difficulty may increase. If the proportion of high-density material B (such as aluminum oxide and magnesium oxide) is too high, these materials usually have high high temperature resistance and low specific heat capacity effect. Too much material B may reduce the specific heat capacity benefit of the overall current collector. In the case of thermal abuse or short circuit of the battery, the specific heat capacity of the current collector may not be sufficient to effectively absorb and delay the reaction heat, thereby reducing the safety performance of the battery and increasing the risk of overheating and thermal failure. A high proportion of material B (such as aluminum oxide and magnesium oxide) usually has high hardness and pressure resistance, but they are difficult to process and may reduce the flexibility of the current collector. A high proportion of material B may increase the difficulty of mechanical processing of the current collector, affect its combination and adaptability with other components of the battery, and affect the overall assembly and stability of the battery. The thermal expansion coefficients of materials A and B may be different. Improper mass ratios may cause mismatched expansion of the materials under temperature changes, which may cause cracks or peeling of the current collector, thereby affecting the long-term stability and safety of the battery.
[0061] Therefore, the appropriate mass ratio of high specific heat capacity material A and material B (1:0.5-1.5) aims to balance heat capacity, heat dissipation performance, material stability and cost. If the mass ratio is too low, it may lead to insufficient heat dissipation and material stability problems; if the mass ratio is too high, it may reduce the specific heat capacity benefit, increase processing difficulty and cause thermal expansion mismatch. By adjusting the ratio of these two materials, the performance of lithium-ion battery current collectors can be optimized and the safety and reliability of batteries under high temperature and thermal abuse conditions can be improved.
[0062] In combination with the first aspect, in some embodiments of the present invention, the mass ratio of high specific heat capacity material A to high compaction material B is 1:0.5. When the ratio is this, high specific heat capacity material A accounts for about 66%, and at this time, the pole piece will not deform below 4 compaction, ensuring the highest specific heat capacity. If the value is lower than 0.5, the pole piece will deform, and if the value is higher than 1.5, the overall specific heat capacity is low, and the hot box and high temperature outer short become worse.
[0063] In combination with the first aspect, in some embodiments of the present invention, when the current collector is a positive electrode current collector, the metal layer is an aluminum layer.
[0064] In combination with the first aspect, in some embodiments of the present invention, when the current collector is a negative electrode current collector, the metal layer is a copper layer.
[0065] In combination with the first aspect, in some embodiments of the present invention, the thickness of the substrate is 1.5 μm to 2.5 μm.
[0066] In combination with the first aspect, in some embodiments of the present invention, the thickness of the substrate is any value of 1.5 μm, 2.0 μm, 2.5 μm, or a range formed by any two of them.
[0067] In combination with the first aspect, in some embodiments of the present invention, the thickness of the metal layer is 4 μm to 6 μm.
[0068] In combination with the first aspect, in some embodiments of the present invention, the thickness of the metal layer is any one of 4 μm, 5 μm, 6 μm, or a range formed by any two of them.
[0069] In combination with the first aspect, in some embodiments of the present invention, the specific heat capacity of the high specific heat capacity material A is between 1 J / g·K and 2.4 J / g·K.
[0070] The specific heat capacity of high specific heat capacity material A is between 1J / g·K and 2.4J / g·K. High specific heat capacity material A has a higher specific heat capacity and can absorb more heat per unit mass. This means that the material can store more heat energy when the temperature rises, reducing the sharp rise in temperature. Furthermore, by effectively absorbing and storing the heat of reaction, high specific heat capacity material A helps to delay the rapid rise in temperature inside the battery, thereby reducing the risk of thermal failure and overheating. It can be understood that in electronic devices such as lithium-ion batteries, high specific heat capacity materials can alleviate the sudden temperature rise caused by thermal abuse or external short circuit. By absorbing and storing the generated heat, they can slow down the temperature rise rate and enhance the thermal stability and safety of the equipment. Furthermore, high specific heat capacity materials can effectively alleviate the impact of thermal shock on the battery and reduce the probability of thermal failure under high temperature conditions. The presence of high specific heat capacity materials helps to keep the temperature of the battery stable and reduce the failure of materials or battery structures caused by drastic temperature changes. Specifically, in a high temperature environment or when an internal chemical reaction occurs in the battery, high specific heat capacity materials can absorb and stabilize the generated heat, thereby reducing the drastic fluctuations in the internal temperature of the battery. This stability is critical to improving the safety and reliability of the battery. Furthermore, by using materials with higher specific heat capacity, the energy storage capacity of the overall system in thermal management can be improved. This helps to achieve better thermal management effects at the same volume, which may increase the energy density of the device. It can be understood that high specific heat capacity materials can provide higher thermal energy storage capacity without adding additional volume. This means that the energy density and performance of the device can be maintained or improved within a limited space. Some high specific heat capacity materials (such as high melting point paraffin) not only have high specific heat capacity, but also have good thermal conductivity. This helps to more effectively transfer heat from the heat source to the heat dissipation area, improving the overall thermal management performance. Materials with high specific heat capacity can effectively conduct heat while absorbing heat. By optimizing the heat conduction path, these materials help to dissipate heat from the inside of the battery faster, further improving the thermal stability of the device. In addition, high specific heat capacity materials can maintain a smaller temperature change when heat is input, thereby reducing the thermal expansion effect of the material. These materials generally have good high temperature resistance and can still maintain their physical and chemical stability under high temperature conditions. In high-temperature operating environments, high specific heat capacity materials can reduce material deformation or failure due to thermal expansion and enhance the long-term stability and reliability of the material. This can effectively extend the service life of the equipment and reduce maintenance requirements.
[0071] Therefore, the specific heat capacity of high specific heat capacity material A is within the range of 1 J / g·K to 2.4 J / g·K, which can significantly improve the thermal management capability, safety performance, energy density and structural stability of electronic devices (such as lithium-ion batteries). By optimizing the use of these materials, the thermal stability of the equipment can be effectively improved, the service life can be extended, and the overall performance can be improved.
[0072] In combination with the first aspect, in some embodiments of the present invention, the specific heat capacity of the high-density material B is between 0.75 J / g·K and 0.90 J / g·K.
[0073] The specific heat capacity of high-density material B is between 0.75 J / g·K and 0.90 J / g·K. Compared with high-specific heat capacity material A (specific heat capacity range 1 J / g·K to 2.4 J / g·K), although the specific heat capacity is lower, high-density material B (such as aluminum oxide and magnesium oxide) generally has high high temperature resistance and chemical stability. These materials can maintain their structural stability in high temperature environments to prevent thermal expansion and material deformation. Furthermore, although the specific heat capacity of high-density material B is lower than that of material A, it performs better in terms of high temperature resistance and structural stability. Material B is mainly used to improve thermal stability and high temperature resistance, while material A focuses more on heat capacity and thermal energy storage capacity. High-density material B (such as aluminum oxide and magnesium oxide) has high hardness and strength, which can improve the mechanical properties of current collectors or other components. These materials have strong wear resistance, which helps to extend the service life of materials and equipment. The mechanical properties (such as hardness and wear resistance) of high-density material B are generally better than those of material A, despite its lower specific heat capacity. Material A's advantage lies in heat capacity, while Material B provides better structural and mechanical properties.
[0074] Therefore, the specific heat capacity of high-density material B is in the range of 0.75 J / g·K to 0.90 J / g·K, mainly providing beneficial effects such as enhanced high temperature resistance, mechanical strength, cost reduction, and improved thermal conductivity efficiency. Compared with high specific heat capacity material A (specific heat capacity 1 J / g·K to 2.4 J / g·K), material B focuses on improving the high temperature stability and economy of the material, while material A focuses on increasing heat capacity and thermal energy storage capacity. By rationally matching and using these two types of materials, better thermal management and equipment performance can be achieved.
[0075] In combination with the first aspect, in some embodiments of the present invention, the compacted density of the high specific heat capacity material A is 1.3 g / cm 3 ~1.8g / cm 3 .
[0076] In combination with the first aspect, in some embodiments of the present invention, the compaction density of the high compaction material B is 4 g / cm 3 ~6.0g / cm 3 .
[0077] The compacted density of high specific heat material A is 1.3 g / cm 3 ~1.8g / cm 3, a lower compaction density means that more materials can be accommodated or designed into lighter components in the same volume. This can effectively utilize space and is suitable for applications that require weight reduction or compact design. It can be understood that in lithium-ion batteries or other electronic devices, the use of low-density material A can help reduce the weight of the overall device while maintaining good thermal management capabilities, which is particularly suitable for portable electronic devices and lightweight design requirements. Further, low-density materials generally have better processability and can be more easily molded and processed. This makes them more suitable for applications with complex shapes or delicate processing. It can be understood that during the production process, lower-density material A is easy to process and mold, and can produce more complex structures or components, which is very important for applications that require high precision and complex designs. Furthermore, lower-density materials generally have better thermal insulation properties, which can effectively isolate heat and reduce heat conduction. This helps to improve the overall thermal management effect, especially in application scenarios that require thermal insulation. It can be understood that in some electronic devices that require effective thermal insulation, low-density material A can reduce heat conduction, thereby protecting other components from excessive temperatures and improving the overall thermal management performance of the device. Furthermore, the production and processing costs of low-density materials are generally low, especially in large-scale production, which can effectively reduce the overall production cost. It can be understood that the raw material and processing costs of low-density material A are low, so that the overall cost can be significantly reduced in large-scale production, which is suitable for economical design and cost-sensitive application scenarios.
[0078] The compaction density of high compaction material B is 4g / cm 3 ~6.0g / cm 3, a higher compaction density means that material B has higher hardness and strength, can withstand greater pressure and mechanical loads, and enhances its durability. It can be understood that in applications that need to withstand high pressure or high stress, such as battery current collectors or mechanical structures, the high density of material B provides superior mechanical properties and durability, preventing the material from deforming or breaking during use. Further, higher density materials generally have better thermal conductivity, can conduct heat more effectively, and help optimize thermal management and heat dissipation. It can be understood that in high temperature or high heat load applications, the high density and good thermal conductivity of material B can quickly conduct heat away from the heat source, prevent local overheating, and improve the overall thermal management efficiency. In addition, high-density materials generally have a larger heat capacity and can store more heat in the same volume, which helps to balance heat changes and reduce temperature fluctuations. It can be understood that the high density and large heat capacity of material B enable it to absorb and store heat more effectively under high temperature conditions, and is suitable for use in applications that require stable temperatures to prevent thermal failure due to rapid temperature changes. Furthermore, the volume density of the high-density material improves the overall structural stability of the material, making it more stable in high temperature or high pressure environments and reducing deformation or degradation of the material. It can be understood that in applications requiring high structural stability (such as battery current collectors in high temperature environments), the high density of material B can improve the stability of the material and ensure the reliability and durability of the device under harsh conditions.
[0079] Therefore, the high specific heat capacity material A (1.3g / cm 3 ~1.8g / cm 3 )'s low density helps reduce weight, improve processing flexibility, improve thermal insulation performance and reduce production costs, and is suitable for applications that require lightweight, complex processing and thermal insulation performance. High-density material B (4g / cm 3 ~6.0g / cm 3 )'s high density helps to enhance mechanical strength and pressure resistance, improve thermal conductivity, optimize heat capacity and enhance structural stability, making it suitable for applications requiring high pressure resistance, high thermal conductivity and stability.
[0080] It should also be noted that the two blends can ensure a higher specific heat capacity while, as an intermediate layer, during the film making and rolling process, the aluminum layer will not rupture due to excessive force on the intermediate layer, leaking out the intermediate filler and damaging the pole piece.
[0081] In a second aspect, in some embodiments of the present invention, a method for preparing the current collector of the first aspect of the present invention is provided, comprising the following steps:
[0082] S1: After mixing the powders of high specific heat capacity material A and high compaction material B in proportion, adding epoxy resin and curing agent, stirring, and curing and molding in a mold to obtain a matrix;
[0083] S2: Arrange a metal layer on the surface of the substrate to obtain a current collector.
[0084] It can be understood that the preparation method of the present invention does not require expensive equipment and complex process control, the reaction conditions are not harsh, the raw materials are easily available, the production cost is low, and it is easy to industrialize production.
[0085] It can also be understood that the preparation method of the current collector of the present invention can ensure the uniform distribution of these materials in the matrix by mixing the high specific heat capacity material A (such as potassium nitrate, high melting point paraffin, carbon nanotubes) and the high compaction material B (such as aluminum oxide, magnesium oxide) in proportion, and mixing them with epoxy resin and curing agent. This helps to achieve uniform thermal properties of the matrix and improve the overall performance of the current collector. The matrix material forms a strong composite structure through solidification, which can provide stable thermal protection performance and avoid performance fluctuations caused by material inhomogeneity.
[0086] It should be noted that the use of epoxy resin and curing agent gives the matrix high mechanical strength and wear resistance, which helps to enhance the structural stability and durability of the current collector in the battery. The cured matrix can better withstand the mechanical stress and thermal expansion inside the battery, improving the long-term performance of the current collector.
[0087] The preparation method of the current collector of the present invention utilizes a simple stirring and curing process, does not require expensive equipment and complex process control, and reduces the technical difficulty and cost in production. The high specific heat capacity materials (such as potassium nitrate, high melting point paraffin, carbon nanotubes, aluminum oxide, magnesium oxide) and epoxy resin and other raw materials used are easy to obtain, which reduces the difficulty and cost of raw material procurement.
[0088] Furthermore, different mold shapes can be selected according to actual needs, and the design of the current collector can be flexibly adjusted to better adapt to batteries of different specifications and sizes. Since the curing process is relatively simple, the dependence on post-processing technology is reduced, further reducing the complexity of production. The use of epoxy resin and curing agent is relatively environmentally friendly, and no large amount of harmful gases or waste will be generated during the production process, which helps to reduce environmental pollution. The application of high specific heat capacity materials improves the thermal management performance of the current collector, making the battery safer under overheating conditions and reducing the risk of thermal runaway of the battery.
[0089] The current collector prepared by the method of the present invention can effectively absorb and slowly release the reaction heat inside the battery cell, enhance the battery's adaptability to thermal shock, and improve the safety and reliability of the battery in a high temperature environment. Through the design of high specific heat capacity, the temperature rise inside the battery cell can be effectively delayed, providing better thermal control capabilities and improving the overall safety of the battery. Therefore, the preparation method of the present invention can not only reduce costs and complexity in production, but also improve the mechanical strength, performance stability, process adaptability and environmental friendliness of the current collector, while enhancing the thermal management capabilities and safety of the battery. These advantages make the preparation method have good industrial application prospects.
[0090] In conjunction with the second aspect, in some embodiments of the present invention, the curing agent includes a polythiol-modified amine.
[0091] Polythiol modified amine is a highly flexible curing agent that can keep the substrate flexible and facilitate production and processing.
[0092] In a third aspect, some embodiments of the present invention provide a lithium-ion battery pole piece, comprising the current collector of the second aspect of the present invention and an active material layer disposed on the surface of the current collector.
[0093] It can be understood that the lithium-ion battery pole piece of the present invention improves the thermal management capability of the battery due to the use of the current collector of the present invention. Since the current collector uses a high specific heat capacity material, it can effectively absorb and slowly release the heat generated inside the battery, thereby slowing down the temperature rise of the battery and improving the thermal stability and safety of the battery. By improving the thermal management of the battery, the risk of thermal runaway is reduced and the safety performance of the battery under high temperature or thermal abuse conditions is enhanced.
[0094] In addition, the mechanical strength and durability of the battery are enhanced. The high mechanical strength and wear resistance of the current collector provide good support, ensuring the stability of the active material layer during the charge and discharge process, and avoiding the problem of battery performance being affected by the falling off or peeling of the pole piece. The combination of a solid matrix structure and a highly durable active material layer improves the cycle life and long-term reliability of the battery.
[0095] The electrical performance of the battery is optimized. The metal layer of the current collector ensures good electrical conductivity of the pole piece, reduces internal resistance, and improves the charge and discharge efficiency of the battery. Good electrical conductivity helps to improve the energy density and power density of the battery. The close combination of the current collector and the active material layer makes the current more evenly distributed on the pole piece, reduces local hot spots and uneven current density, and thus improves the overall performance of the battery.
[0096] The production process is simplified. The preparation method of the current collector is relatively simple, without the need for expensive equipment and complex process control, which makes the production cost of the pole piece low and suitable for large-scale industrial production. The materials used (such as high specific heat capacity materials, epoxy resin, etc.) are easy to obtain, further reducing the production cost and difficulty.
[0097] Improved the overall performance of the battery. Combining high specific heat capacity current collectors and high-quality active material layers can significantly improve the performance of the battery under thermal shock and high temperature external short conditions, making the battery more stable and reliable. The use of high specific heat capacity materials and high temperature resistant materials improves the performance of the battery in high temperature environments, making the battery more suitable for working under extreme conditions.
[0098] Optimized battery safety. Through effective heat absorption and dissipation, the temperature rise inside the battery is slowed down, which helps prevent the battery from catching fire or exploding in the event of overheating or short circuit. The improved current collector design and active material layer combination improve the environmental adaptability of the battery and adapt to the performance requirements under various usage conditions.
[0099] Improved battery consistency and reliability. Because unified materials and methods are used in the manufacturing process, the performance consistency of each pole piece can be ensured, improving the overall reliability and stability of the battery.
[0100] Thus, the lithium-ion battery pole piece of the present invention, by combining a high specific heat capacity current collector and a high-performance active material layer, brings about significant improvement in thermal management, enhanced mechanical strength, optimized electrical performance, simple production, improved comprehensive performance, improved safety, and enhanced consistency and reliability. These advantages enable the battery pole piece to provide higher performance and better safety assurance in practical applications.
[0101] In combination with the third aspect, in some embodiments of the present invention, when the lithium-ion battery electrode sheet is a positive electrode sheet, the components of the active material layer include a positive electrode material, a positive electrode conductor and a positive electrode binder.
[0102] In combination with the third aspect, in some embodiments of the present invention, the positive electrode material includes lithium cobalt oxide.
[0103] In combination with the third aspect, in some embodiments of the present invention, the positive electrode conductive agent includes acetylene black.
[0104] In combination with the third aspect, in some embodiments of the present invention, the positive electrode binder includes polyvinylidene fluoride.
[0105] In combination with the third aspect, in some embodiments of the present invention, the mass ratio of the positive electrode material, the positive electrode conductor and the positive electrode binder can be 98:1.2:0.8.
[0106] In combination with the third aspect, in some embodiments of the present invention, a method for preparing a positive electrode sheet includes:
[0107] The positive electrode material, positive electrode conductive agent and positive electrode binder are fully stirred and mixed in an N-methylpyrrolidone solvent system, and then coated on an aluminum foil, and then dried, rolled and slit to obtain a positive electrode sheet.
[0108] In combination with the third aspect, in some embodiments of the present invention, when the lithium-ion battery pole piece is a negative pole piece, the components of the active material layer include a negative electrode material, a negative electrode conductor, a negative electrode binder and a thickener.
[0109] In combination with the third aspect, in some embodiments of the present invention, the negative electrode material includes graphite.
[0110] In combination with the third aspect, in some embodiments of the present invention, the negative electrode conductive agent includes acetylene black.
[0111] In combination with the third aspect, in some embodiments of the present invention, the negative electrode binder includes styrene-butadiene rubber.
[0112] In conjunction with the third aspect, in some embodiments of the present invention, the thickener includes sodium carboxymethyl cellulose.
[0113] In combination with the third aspect, in some embodiments of the present invention, the mass ratio of the negative electrode material, the negative electrode conductor, the negative electrode binder and the thickener can be 98.1:0.5:0.7:0.7.
[0114] In combination with the third aspect, in some embodiments of the present invention, a method for preparing a negative electrode sheet includes:
[0115] The negative electrode material, negative electrode conductive agent, negative electrode binder and thickener are fully stirred and mixed in a deionized water solvent system, and then coated on a copper foil, and then dried, rolled and slit to obtain a negative electrode sheet.
[0116] In a fourth aspect, in some embodiments of the present invention, a lithium-ion battery is provided, comprising a separator, an electrolyte, and the lithium-ion battery pole piece of the third aspect of the present invention, wherein the lithium-ion battery pole piece comprises a positive pole piece and a negative pole piece.
[0117] It is easy to understand that the lithium-ion battery of the present invention has improved thermal management capabilities. Since the current collector uses a high specific heat capacity material (such as potassium nitrate, high melting point paraffin, carbon nanotubes and aluminum oxide, magnesium oxide composite materials), the battery can more effectively absorb and disperse the heat generated during the charging and discharging process. This helps to keep the battery within a safe operating temperature range and avoid safety issues caused by overheating. The improved thermal management design can slow down the temperature rise inside the battery and reduce the risk of the battery under high temperature or thermal abuse conditions.
[0118] It can also be understood that the lithium-ion battery of the present invention enhances the safety of the battery. The improved current collector can better manage heat, reduce the risk of thermal runaway of the battery under high temperature or short circuit conditions, and reduce the possibility of battery fire or explosion. Furthermore, the use of high specific heat capacity materials improves the thermal stability of the battery in extreme environments, making the battery safer and more reliable.
[0119] Furthermore, the mechanical strength and durability of the battery are improved. The high mechanical strength of the current collector and the good combination of the active material layer provide a stable structural support, making the battery more durable during use and reducing the situation of pole piece shedding or peeling. In addition, the durable material and structural design help to extend the cycle life and overall service life of the battery.
[0120] The lithium-ion battery of the present invention optimizes the electrical performance of the battery. The excellent conductivity of the current collector and the high conductivity of the active material layer improve the overall conductivity of the battery, reduce the internal resistance, and thus improve the charging and discharging efficiency and power density. Furthermore, the good combination of the current collector and the active material layer ensures the uniform distribution of the current on the pole piece, reduces local hot spots, and improves the consistency and stability of the battery performance.
[0121] The lithium-ion battery of the present invention simplifies the production process. The preparation method of the current collector is simple, the raw materials are easily available and the production cost is low, making the entire production process more economical and suitable for large-scale industrial production. It can be understood that the simplified process reduces the need for complex equipment and fine processes, making the production process more efficient.
[0122] The lithium-ion battery of the present invention has improved environmental adaptability. The improved thermal management and mechanical strength make the battery more stable and more adaptable under various extreme environmental conditions (such as high temperature, low temperature, etc.). It also improves the performance of the battery under high temperature and high current density conditions, and increases the reliability of the battery in various application scenarios.
[0123] The lithium-ion battery of the present invention enhances the consistency and reliability of the battery. Since uniform materials and methods are used in the manufacturing process, the consistency of each battery pole piece is ensured, and the overall performance and reliability of the battery are improved. The optimized design and material selection improve the reliability of the battery, reduce the failure rate, and improve the product quality.
[0124] In general, lithium-ion batteries using the battery pole pieces of the present invention have significant advantages in thermal management, safety, mechanical strength, electrical performance, production cost, environmental adaptability, consistency and reliability. These improvements make the battery perform better in practical applications and can better meet the high performance and safety requirements of modern battery applications.
[0125] In combination with the fourth aspect, in some embodiments of the present invention, the isolation membrane includes a polyethylene (PE) porous polymer film.
[0126] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0127] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0128] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0129] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0130] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0131] The specific heat capacity of potassium nitrate is 1.34 J / (g·K).
[0132] The specific heat capacity of alumina is 0.75 J / (g·K).
[0133] The specific heat capacity of high melting point paraffin is 2.4 J / (g·K).
[0134] The specific heat capacity of carbon nanotubes is 1.0 J / (g·K).
[0135] The specific heat capacity of magnesium oxide is 0.90 J / (g·K).
[0136] Example 1
[0137] In this embodiment, the current collector is first prepared, then the pole piece is prepared, and finally the lithium-ion battery is prepared. The specific process is:
[0138] (1) Current collector preparation
[0139] Preparation of high specific heat capacity material fillers
[0140] The high specific heat capacity material A (potassium nitrate) is compounded with the high compaction material B (aluminum oxide), and the specific method is as follows:
[0141] The powders of material A and material B are mixed evenly in a mass ratio of 1:1, and the epoxy resin and polythiol-modified amine (curing agent with strong flexibility) are stirred and fully mixed in a mass ratio of 10:1, and then poured into the composite material powder, and slowly stirred with a low-speed stirrer (such as a scraper or a paddle stirrer) to form a uniform mixture, and then placed in a polytetrafluoroethylene groove (groove depth 2um) mold and cured at room temperature to obtain a molded composite material substrate:
[0142] 1) Preparation of positive electrode current collector: The formed composite material substrate is plated with a 5-micron aluminum layer on the surface of the composite material by a physical vapor deposition method of magnetron sputtering to obtain a positive electrode current collector;
[0143] 2) Preparation of negative electrode current collector: The formed composite material substrate is plated with a 5-micron copper layer by electroplating to obtain a negative electrode current collector.
[0144] Foil cross-section view Figure 1 shown. Figure 1 In the figure, 100 is the metal layer and 200 is the substrate. The metal layer is 5 microns, the filler (i.e., the substrate) is about 2 microns, and the total thickness is 12 microns.
[0145] (2) Preparation of positive electrode sheet
[0146] The positive electrode material lithium cobalt oxide, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in an N-methylpyrrolidone solvent system at a mass ratio of 98:1.2:0.8, and then coated on an aluminum foil, dried, and rolled (rolling density 4.0 g / cm 3 ) and obtain the positive electrode sheet after stripping.
[0147] (3) Preparation of negative electrode sheet
[0148] The negative electrode material, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were fully stirred and mixed in a deionized water solvent system at a mass ratio of 98.1:0.5:0.7:0.7, and then coated on a copper foil, dried, and rolled (rolling density 1.65 g / cm 3 ) and obtain the negative electrode sheet after slitting.
[0149] (4) Preparation of isolation membrane
[0150] A polyethylene (PE) porous polymer film is used as the isolation membrane.
[0151] (5) Preparation of electrolyte
[0152] Lithium salt LiPF 6 A solution prepared with a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 25:25:15:31:4, mass ratio) in a mass ratio of 8:92 is used as the electrolyte of the lithium battery.
[0153] (6) Preparation of lithium-ion secondary batteries
[0154] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of safety isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in a packaging shell, and the electrolyte is injected and packaged to obtain a lithium battery.
[0155] Example 2
[0156] The difference from Example 1 is that the high specific heat capacity material A is high melting point paraffin.
[0157] Example 3
[0158] The difference from Example 1 is that the high specific heat capacity material A is carbon nanotubes.
[0159] Example 4
[0160] The difference from Example 1 is that the high-density material B is magnesium oxide.
[0161] Example 5
[0162] The difference from Example 1 is that the high specific heat capacity material A is high melting point paraffin, and the high compaction material B is magnesium oxide.
[0163] Example 6
[0164] The difference from Example 1 is that the high specific heat capacity material A is carbon nanotubes, and the high compaction material B is magnesium oxide.
[0165] Example 7
[0166] The difference from Example 1 is that the high specific heat capacity material A is carbon nanotubes, the high compaction material B is magnesium oxide, and the mass ratio of the high specific heat capacity material A to the high compaction material B is 1:0.5.
[0167] Comparative Example 1
[0168] The difference from Example 1 is that the high specific heat capacity material A and the high compaction material B are not added, and the matrix is a full metal current collector, that is, the positive electrode is pure aluminum metal, and the negative electrode is pure copper metal.
[0169] Comparative Example 2
[0170] The difference from Example 1 is that the high specific heat capacity material A is not added to the molded composite material substrate.
[0171] Comparative Example 3
[0172] The difference from Example 1 is that the high-density material B is not added to the molded composite material substrate.
[0173] Comparative Example 4
[0174] The difference from Example 1 is that the high specific heat capacity material A is carbon nanotubes, the high compaction material B is magnesium oxide, and the mass ratio of the high specific heat capacity material A to the high compaction material B is 1:0.1.
[0175] Comparative Example 5
[0176] The difference from Example 1 is that the high specific heat capacity material A is carbon nanotubes, the high compaction material B is magnesium oxide, and the mass ratio of the high specific heat capacity material A to the high compaction material B is 1:3.
[0177] Comparative Example 6
[0178] The difference from Example 1 is that the base layer is a high molecular PET layer.
[0179] Safety performance test
[0180] Relevant performance tests were performed on the batteries prepared in Examples 1 to 6 and the comparative example.
[0181] (1) Lithium-ion battery thermal abuse performance test
[0182] The lithium-ion batteries were placed in a 25°C constant temperature chamber for 30 minutes to allow the lithium-ion batteries to reach a constant temperature. The lithium-ion batteries that reached a constant temperature were charged at a constant current of 0.5C to a voltage of 4.53V, and then charged at a constant voltage of 4.53V to a current of 0.05C, and left for 60 minutes. The cells were placed in an X°C (X=126, 128, 130, 132, 134, 136, 138, 140) oven, and the oven temperature was raised to X°C at a rate of 5±2°C / min, and kept for 30 minutes before stopping. During the process, the cell surface temperature, ambient temperature and voltage were monitored.
[0183] (2) High temperature external short performance test of lithium-ion batteries
[0184] Place the lithium-ion batteries in a 25℃ constant temperature chamber and let them stand for 30 minutes to allow the lithium-ion batteries to reach a constant temperature. Charge the lithium-ion batteries that have reached a constant temperature at a constant current of 0.5C to a voltage of 4.53V, then charge them at a constant voltage of 4.53V to a current of 0.05C, and leave them for 60 minutes. Put the cells in a 57±4℃ oven (the temperature chamber is set at 61 degrees). When the surface temperature of the cells reaches 57±4℃, leave them for 30 minutes; short-circuit the positive and negative electrodes of the cells with a load of resistance X±5mΩ (X=80, 60, 50, 40), and monitor the surface temperature and voltage of the cells. The test terminates when one of the following two situations occurs: a. The cell temperature drops to 20% lower than the peak value; b. The short-circuit time reaches 24h.
[0185] The specific test data is shown in Table 1.
[0186] Table 1
[0187] serial number Hot box passing temperature ℃ High temperature external short through internal resistance mΩ Example 1 134 50 Example 2 136 40 Example 3 132 50 Example 4 134 50 Example 5 136 40 Example 6 132 50 Example 7 132 60 Comparative Example 1 126 Invalidation Comparative Example 2 128 80 Comparative Example 3 Unable to prepare samples Unable to prepare samples Comparative Example 4 Unable to prepare samples Unable to prepare samples Comparative Example 5 128 60 Comparative Example 6 130 50
[0188] From the results in Table 1, it can be seen that the lithium-ion battery using the current collector of the present invention has the following significant advantages over the comparative example in terms of hot box passing temperature and high-temperature external short internal resistance:
[0189] Higher hot box pass temperature. The hot box pass temperature of the embodiment is 130°C to 136°C, which is much higher than 126°C of the comparative example. The batteries of the embodiment are able to pass the hot box test at a higher temperature, which means that they have stronger thermal stability under high temperature conditions. The hot box test is an important indicator for evaluating the performance of batteries under overheating conditions. The higher pass temperature indicates that the batteries of the embodiment can maintain better performance and safety when facing high temperature external short or thermal abuse. The higher hot box pass temperature also shows that the batteries of the embodiment are more tolerant in high temperature environments, reducing the risk of thermal runaway at high temperatures.
[0190] Lower high-temperature external short circuit internal resistance. The high-temperature external short circuit internal resistance of the embodiment is 40mΩ to 80mΩ, indicating that the battery of the embodiment has better electrical conductivity and less thermal runaway risk. Batteries with low internal resistance can conduct current more effectively under high temperature or external short circuit conditions, reducing overheating problems caused by excessive internal resistance. Lower internal resistance generally means higher charging and discharging efficiency of the battery and less energy loss. The battery of the embodiment can maintain a lower internal resistance under high temperature conditions, indicating that its battery design and materials can better maintain performance and stability under high temperature conditions.
[0191] In Comparative Example 1, no high specific heat capacity material A and high compaction material B were added, and the matrix was an all-metal current collector, that is, the positive electrode was pure aluminum metal, and the negative electrode was pure copper metal. Although pure aluminum and copper have good thermal conductivity, their specific heat capacity is low and they cannot effectively absorb and store reaction heat. Under high temperature conditions, the heat generated inside the battery will accumulate rapidly, causing the temperature to rise rapidly. Therefore, the temperature of the hot box is only 126°C, and the high-temperature external short fails through internal resistance.
[0192] In the composite material substrate formed in Comparative Example 2, high specific heat capacity material A is not added. The presence of high specific heat capacity material helps to absorb and disperse the reaction heat generated under high temperature or short circuit conditions to prevent overheating of the material. Since high specific heat capacity material A is not added, the temperature of the hot box passing through is only 128°C, and the high-temperature external short circuit passes through an internal resistance of 80mΩ.
[0193] In Comparative Example 3, high-density material B was not added, and high-specific heat capacity material A alone was not pressure-resistant. During the rolling process, the pole piece was deformed and broken, resulting in the inability to prepare samples.
[0194] In Comparative Example 4, the high specific heat capacity material A is carbon nanotubes, the high compaction material B is magnesium oxide, and the mass ratio of the high specific heat capacity material A to the high compaction material B is 1:0.1, which exceeds the ratio range of 1:0.5 to 1.5 specified in the present invention. A uniform substrate cannot be effectively formed, which affects the structural integrity and performance of the material and results in the inability to prepare samples.
[0195] In Comparative Example 5, the high specific heat capacity material A is carbon nanotubes, the high compaction material B is magnesium oxide, and the mass ratio of the high specific heat capacity material A to the high compaction material B is 1:3, which exceeds the ratio range of 1:0.5 to 1.5 specified in the present invention. Excessive magnesium oxide content will affect the thermal conductivity and mechanical strength of the composite material, making it impossible to effectively absorb and dissipate the reaction heat, thereby reducing the safety performance of the battery. Therefore, the hot box pass temperature is 128°C, and the high-temperature external short pass internal resistance is 60mΩ.
[0196] Although the hot box passing temperature of Comparative Example 6 is 130°C, since the base layer is a high-molecular PET layer, although it has good ductility, it has poor pressure resistance, and there are problems such as easy cracking and deformation and the inability to weld the tabs.
[0197] Compared with the comparative example, the embodiment has the following main advantages:
[0198] Higher thermal stability: Able to maintain stability at higher temperatures, passing higher temperatures in hot box testing, demonstrating superior thermal management performance.
[0199] Better high-temperature safety: The internal resistance in the high-temperature short-circuit test is significantly reduced, indicating that the battery can effectively control the internal resistance under high-temperature conditions, reducing the risk of thermal runaway and improving safety.
[0200] Higher performance stability: Lower internal resistance and higher thermal stability mean that the embodiment battery can provide more reliable performance and longer service life in actual use.
[0201] These advantages indicate that the battery of the embodiment excels in safety, performance stability and adaptability under high temperature conditions, and is suitable for use in application environments with higher requirements.
[0202] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A current collector, characterized in that: It includes a substrate and a metal layer arranged on the surface of the substrate, wherein the components of the substrate include a high specific heat capacity material A and a high-density material B, wherein the high specific heat capacity material A includes at least one of potassium nitrate, high-melting point paraffin and carbon nanotubes, and the high-density material B includes at least one of aluminum oxide and magnesium oxide.
2. The current collector according to claim 1, characterized in that: The mass ratio of the high specific heat capacity material A to the high compaction material B is 1:0.5-1.
5.
3. The current collector according to claim 1, characterized in that: When the current collector is a positive electrode current collector, the metal layer is an aluminum layer; and / or when the current collector is a negative electrode current collector, the metal layer is a copper layer.
4. The current collector according to claim 1, characterized in that: The thickness of the substrate is 1.5 μm to 2.5 μm; and / or the thickness of the metal layer is 4 μm to 6 μm.
5. The current collector according to claim 1, characterized in that: The specific heat capacity of the high specific heat capacity material A is 1.0 / g·K to 2.4 J / g·K; and / or the specific heat capacity of the high compacted material B is 0.75 J / g·K to 0.90 J / g·K; and / or the compacted density of the high specific heat capacity material A is 1.3 g / cm 3 ~1.8g / cm 3 ; and / or, the compaction density of the high compaction material B is 4g / cm 3 ~6.0g / cm 3 .
6. A method for preparing a current collector as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1: mixing the powders of the high specific heat capacity material A and the high compaction material B in proportion, adding epoxy resin and curing agent, stirring, and curing and molding in a mold to obtain the matrix; S2: Arranging the metal layer on the surface of the substrate to obtain the current collector.
7. The method according to claim 6, characterized in that The curing agent includes a polythiol-modified amine.
8. A lithium-ion battery pole piece, characterized in that: The invention comprises the current collector according to any one of claims 1 to 5 and an active material layer arranged on the surface of the current collector.
9. The lithium-ion battery pole piece according to claim 8, characterized in that: When the lithium-ion battery pole piece is a positive pole piece, the components of the active material layer include a positive electrode material, a positive electrode conductor and a positive electrode binder; and / or, when the lithium-ion battery pole piece is a negative electrode pole piece, the components of the active material layer include a negative electrode material, a negative electrode conductor, a negative electrode binder and a thickener.
10. A lithium ion battery, characterized in that: It comprises a separator, an electrolyte and the lithium-ion battery pole piece according to claim 8, wherein the lithium-ion battery pole piece comprises a positive pole piece and a negative pole piece.